The gap between formal education and ecotourism in Penang / Song-Quan Ong, Hamdan Ahmad and Zairi Jaal - Ong, Song-Quan; Ahmad, Hamdan; Jaal, Zairi (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
The development of ecotourism in Penang has to acquire environmental knowledge. We aimed to determine the supply, demand and career pathway for the environmental program in Penang. All the programs of Higher Education Providers (HEPs) were analyzed, market demand was conducted on the high schools’ students of Penang empirically, and the career pathways were evaluated from essential recruitment companies. There are 84 tertiary education institutions in the Northern Peninsular Malaysia (five public universities, ten private universities, eight university colleges, and 61 colleges), but only three institutions provided environmental or related undergraduate programs; 13 institutions consisted of tourism management programs, but not specific in ecotourism. For the demand investigation, a program survey was conducted on 206 students with age between 16-19 (Form 4, 5, 6 and A-level); more than 58% of the students showed favorable to the environmental programs. However, the job opportunities related to the environment were significantly fewer compared to other occupations; this might be the reason for fewer programs in HEPs. Development of ecotourism in Penang must be equipped with the environmental knowledge to bring the true meaning of ecotourism--to protect nature, empower the local people, and educate the local population and the ecotourist.